2018
DOI: 10.1002/ecs2.2406
|View full text |Cite
|
Sign up to set email alerts
|

Eutrophication homogenizes shallow lake macrophyte assemblages over space and time

Abstract: Eutrophication is commonly implicated in the reduction in macrophyte species richness in shallow lakes. However, the extent to which other more nuanced measures of macrophyte diversity, such as assemblage heterogeneity, are impacted concurrently by eutrophication over space and time and the joint influences of other factors (e.g., species invasions and connectivity) remains relatively poorly documented. Using a combination of contemporary and paleoecological data, we examine how eutrophication influences macro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 50 publications
8
36
0
Order By: Relevance
“…Sites hydrologically connected to the central lake ( Group 1 ) had the highest species richness and abundances of macrophytes regarded as conservation priorities (Table ; Table S5.1). A companion study by Salgado, Sayer, Brooks, Davidson, Goldsmith, et al () showed that macrophyte communities in this group of connected lakes were also more heterogeneous in species relative abundances and composition than in the less specious and eutrophic isolated lakes. Subsidiary natural water flows from the associated satellite lakes with variable nutrient enrichment conditions may therefore introduce a range of different plant propagules to the central lake while recurrent floods likely also transport plant propagules in the opposite direction.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Sites hydrologically connected to the central lake ( Group 1 ) had the highest species richness and abundances of macrophytes regarded as conservation priorities (Table ; Table S5.1). A companion study by Salgado, Sayer, Brooks, Davidson, Goldsmith, et al () showed that macrophyte communities in this group of connected lakes were also more heterogeneous in species relative abundances and composition than in the less specious and eutrophic isolated lakes. Subsidiary natural water flows from the associated satellite lakes with variable nutrient enrichment conditions may therefore introduce a range of different plant propagules to the central lake while recurrent floods likely also transport plant propagules in the opposite direction.…”
Section: Discussionmentioning
confidence: 89%
“…A further methodological limitation is the lack of data on historical climatic or environmental variables (other than eutrophication and changing water levels and connectivity) that may have played a role in structuring the community over space and time. Nonetheless, as indicated by both macrophyte and invertebrate compositional shifts, it is strongly suspected that these factors were the key drivers of change in the ULE system (Battarbee, ; Salgado, Sayer, Brooks, Davidson, Goldsmith, et al, ; Salgado, Sayer, Brooks, Davidson, & Okamura, ), as is typically the case for Northern Hemisphere lakes.…”
Section: Discussionmentioning
confidence: 99%
“…Such conditions may promote invasive species as ‘passengers’ of change ( sensu MacDougall & Turkington, ) and are likely to favour common native species that employ a more generalist or environmentally tolerant strategy versus rarer species with narrower environmental niches (Devictor, Julliard, & Jiguet, ). There is also extensive evidence of environmental changes driving shifts in macrophyte communities (Jeppesen, Peder Jensen, Søndergaard, Lauridsen, & Landkildehus, ; Sand‐Jensen et al, ) even leading to BH (Salgado et al, ). These mechanisms are not mutually exclusive and multiple processes could be driving the overall patterns we observed.…”
Section: Discussionmentioning
confidence: 99%
“…Studies that have found clear signs of biotic homogenisation for aquatic macrophytes are either considering other biodiversity measurements or beta diversity measures, or are based on paleoecological methods (Salgado et al 2018). There are only a few studies of temporal changes in spatial beta diversity (Winegardner et al 2017, Larsen et al 2018, Wengrat et al 2018) and even fewer considering aquatic macrophytes.…”
Section: Discussionmentioning
confidence: 99%